Analisis Pemanfaatan Repositori untuk Preservasi Pengetahun Nuklir di BATAN - Noeraida Noeraida; Andri Sungkono (Perpustakaan Nasional, 2020)
Since early 2017, librarians have been working with young computer institutions at National Nuclear Energy Agency to develop e-repositories as a web-based knowledge storage medium in the form of nuclear science and technology scientific publications in digital form. Data input is carried out by each work unit. The purpose of this study is to determine the use of institutional repositories that have been developed, management and preservation of knowledge that is expected to increase competence in the effort to create new knowledge. The method used is descriptive analysis. Source of data used as population and object of research are statistical data on repositories from April 2018 to October 22, 2019, which were collected in October-November 2019. Based on the results of the study, all work units have uploaded scientific publications to repositories of 6,190 titles. The most uploaded work units were PAIR 1,082 titles, followed by PSTBM 932 and PRSG 823. The collection type in the repository was 64.56%, Conference or Workshop 23.49%, monograph 8.68% and others 3.28 %. The number of users who downloaded the repository collection was 106,946 times. Comparison between the number of collections uploaded and users who download has a ratio of 1:17. The most downloaded subjects are the nuclear fuel cycle and advanced materials. Users who use repositories from Indonesia amounted to 50.79%, and from other countries in the world namely China, USA, Vietnam, and others amounted to 49.21%. The conclusion in this study is that all work units have utilized optimally by uploading collections to the repository. Internal and external users of BATAN from within and outside the country have utilized it by downloading from the collection of repositories. The results of this study can be an evaluation for stakeholders to manage and add to the collection on an ongoing basis.